Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Project Based Learning (PjBL) Membuat Menara Keberagaman Budaya pada Pembelajaran IPAS Kelas IV Sekolah Dasar - Ibra Sabila Arif; Adrias Adrias; Aissy Putri Zulkarnaini (Lembaga Pengembangan Kinerja Dosen, 2025)
This research is motivated by the problem of the available LKPD still not being This research is motivated by the problem of the available LKPD still not being optimal in terms of development and use so that students are less interested in participating in learning. This is due to the lack of teacher motivation in creating innovative LKPD. Have never developed Student Worksheets (LKPD) based on Project Based Learning (PjBL) in learning, especially in science and science learning. Based on these problems, this research aims to develop PjB-based LKPD for science and science learning in class IV elementary schools that is valid, practical and effective. The type of research carried out is development research using the ADDIE development model. The test school was class IV students at SDN 12 Sintuk Toboh Gadang, while the research school was class IV students at SDN 11 Lubuk Alung. The research results obtained that the LKPD had a material validity level of 84.9%, language validity 88.8%, media validity 87.5% in the valid category. while the practicality test at the trial school obtained a percentage of 93.33%, for the teacher response questionnaire and 93.4% for the student response questionnaire in the very practical category. Furthermore, the practicality test at the research school obtained results of 90% for the teacher response questionnaire and 92.16% for the student response questionnaire in the very practical category. In the LKPD effectiveness test in the trial school the percentage was 89.64% and in the research school the percentage was 93% with both categories being very effective. It can be concluded that PjBL-based LKPD in grade IV elementary school science learning can be declared valid, practical and effective for use in the learning process.